2020
DOI: 10.1016/j.tra.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Non-technological challenges for the remote operation of automated vehicles

Abstract: No existing automated vehicle can operate in all conditions and environments. In order to allow unmanned operation of automated vehicles in all conditions, many developers have the capability for human drivers to operate the vehicle from a remote location using wireless communication. This practice, referred to as remote operation or teleoperation, is prevalent among industry, yet has received little attention in the legal and transportation literature. This paper describes the legal environment for remote ope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Remote operation can be divided into two distinct categories: remote assistance, where the operator only provides routing instructions that are then executed by the vehicle's automated control system, and remote driving, where the operator controls the vehicle's steering, throttle, breaking, signaling, etc. [1]. The requirements for hardware, bandwidth, and networking for implementing remote driving are more demanding than for remote assistance.…”
Section: Remote Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote operation can be divided into two distinct categories: remote assistance, where the operator only provides routing instructions that are then executed by the vehicle's automated control system, and remote driving, where the operator controls the vehicle's steering, throttle, breaking, signaling, etc. [1]. The requirements for hardware, bandwidth, and networking for implementing remote driving are more demanding than for remote assistance.…”
Section: Remote Operationmentioning
confidence: 99%
“…Each country has their own legislation for allowing vehicles to be controlled remotely. In general, many countries have set up laws that would allow remotely operated vehicles on public roads, and for example in most states in the United States, remote operations are viable option for driving as long as the operator has a valid driver's license [1]. Similar legislature has been set on the EU level [10].…”
mentioning
confidence: 99%
“…Existing research has attempted to explore the teleoperation of vehicle automation from different perspectives. Goodall [ 18 ] reviewed the legal environment of the teleoperation of vehicles and developed a model to predict the required number of remote drivers for operating large-scale automated vehicle fleets. The model prediction results indicated that a high proportion of jobs currently belonging to professional human drivers in the USA could potentially be replaced by automated vehicles managed by remote drivers.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is soon going to change. With many modes of transportation already becoming automated or implementing autonomous systems (Goodall 2020;Outay et al 2020), the maritime industry is lagging behind. However, it will eventually catch up-sooner rather than later.…”
Section: Introductionmentioning
confidence: 99%